16.8k views
4 votes
-4 (x + 10) - 6 = -3 (x-2)

I also need help with knowing how to do it. If in you answer you can explain to me how to do it and the answer that would be awesome!

2 Answers

6 votes

Answer:

x = 52

Explanation:

-4(x+10)-6 = -3(x-2)

first use the distributive property, and multiply the -4 by x and +10, and -3 by x and -2

-4x-40-6 = -3x+6

now combine like terms

-4x-46 = -3x+6

now add 46 to both sides

-4x = -3x+52

now add 3x to both sides

-x = 52

now multiply positive 1 to each side

x = 52

User Patryk Czarnik
by
5.1k points
4 votes

-4(x + 10) - 6= -3(x - 2) (remove the parantheses)

-4x - 40 - 6 = -3x + 6 (calculate)

-4x - 46 = -3x + 6 (move the terms)

-4x + 3x = 6 + 46 (collect like terms and calculate)

-x = 52 (change signs)

x = -52

User Jessiah
by
5.5k points